Enhancing the personal identification number input as a means of identification signature - Tee, Elok Robert; Selvanathan, N. (Faculty of Computer Science and Information Technology, University of Malaya, 1996)
The process of typing the personal identification number (PIN) can be broken down into quantifiable components, such as latency time, keypress force, keypress duration and keypress displacement which can be evaluated and used to verify the identity of a person. The keypress pattern is called the PIN signature. As the PIN signature is like the written signature that differs slightly with every execution, a neural-fuzzy application is devised to verify the PIN signature input against the reference profile.